2018
DOI: 10.1016/j.brs.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous rTMS and psychotherapy in major depressive disorder: Clinical outcomes and predictors from a large naturalistic study

Abstract: 1) Combining rTMS and PT resulted in a 66% response and a 56% remission rate at the end of treatment with 60% sustained remission at follow-up. Compared to previous findings in RCTs, these rates are relatively high; 2) No differences were found between the 10 Hz and 1 Hz TMS regarding clinical outcome; 3) Clinical baseline variables were not predictive of treatment outcomes; 4) Early symptom improvement (at session 10) was highly predictive of response, and may therefore be used to guide rTMS + PT continuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 54 publications
5
89
0
Order By: Relevance
“…First, we tested for any effect of stimulation‐group (1 Hz rTMS, sham TMS, 20 Hz rTMS) or/and session (Pre‐TMS, Post‐1‐TMS, Post‐2‐TMS) on mFP‐amygdala‐FC using a 3 × 3 factorial mixed design ANOVA (MD‐ANOVA; see also Donse et al, ). Second, we tested our main hypothesis, that is, that the three stimulation‐groups (1 Hz rTMS, sham TMS, 20 Hz rTMS) would differ in mFP‐amygdala‐FC at the Post‐1‐TMS session compared to the Pre‐TMS session using a 3 × 2 factorial MD‐ANOVA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we tested for any effect of stimulation‐group (1 Hz rTMS, sham TMS, 20 Hz rTMS) or/and session (Pre‐TMS, Post‐1‐TMS, Post‐2‐TMS) on mFP‐amygdala‐FC using a 3 × 3 factorial mixed design ANOVA (MD‐ANOVA; see also Donse et al, ). Second, we tested our main hypothesis, that is, that the three stimulation‐groups (1 Hz rTMS, sham TMS, 20 Hz rTMS) would differ in mFP‐amygdala‐FC at the Post‐1‐TMS session compared to the Pre‐TMS session using a 3 × 2 factorial MD‐ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…First, we tested for any effect of stimulation-group (1 Hz rTMS, sham TMS, 20 Hz rTMS) or/and session (Pre-TMS, Post-1-TMS, Post-2-TMS) on mFP-amygdala-FC using a 3 × 3 factorial mixed design ANOVA (MD-ANOVA; see also Donse et al, 2018). Second, we tested our main hypothesis, that is, that the three stimulation-groups Because the mFP is implicated in a variety of neuronal processes and shows FC with several brain regions, we also conducted an explorative whole brain analysis using a 3 × 2 factorial MD-ANOVA in SPM8 testing for the interaction between stimulation-group (1 Hz rTMS, sham TMS, 20 Hz rTMS) and session (Pre-TMS, Post-1-TMS; see Section 3.4).…”
Section: Subsequent Analyses Focused On Right-mfp-right-amygdala-fcmentioning
confidence: 99%
See 1 more Smart Citation
“…Response rates reached 66%, with no difference between rTMS modalities. 101 Regarding tDCS, a study in a rodent slice model showed that excitatory direct-current stimulation can strengthen cellular mechanisms thought to underlie learning and memory formation (long-term potentiation, LTP 102 ). Critically, this enhancement occurred only when stimulation was applied ''online,'' i.e., during LTP -there was no effect when the identical stimulation was applied ''offline,'' i.e., prior to LTP.…”
Section: Convulsive Modalitiesmentioning
confidence: 99%
“…Non-invasive brain stimulation (NIBS) strategies such as tDCS have exhibited promising effects in decreasing different psychiatric symptoms, either as a stand-alone or combined with pharmacotherapy and psychological interventions (10).…”
mentioning
confidence: 99%